Educação indígena x educação escolar indígena; um aprendizado diferenciado - Mendes, Sâmara Leíla Cunha (2019)
This research aims to study the relationship between the Kayapó indigenous people and the Municipal School of Primary Education Beca, located in the indigenous village Piokrôtikõ in Ourilândia, a town located in the state of Pará. In this way, the aim of this study is to understand how the formal school uses the relationship between indigenous education and the indigenous school education, and how both of them interrelate, considering that the indigenous school education should bring, in this proposal, a differentiated and intercultural treatment which respected the native language with the objective of contributing so that the indigenous school education does not begin to be used as a manner of domination of those people. In order to understand the meaning of schooling, we elucidate the following question: does the formal school carry the threat of impoverishing of the mother tongue, since it emphasizes the writing in portuguese at the expense of oral tradition? This research had, in its first stage, the collection of data centered on the material of pedagogical exercises used in the Beca school and on scheduled interviews with the current teacher of the indigenous village. After that, we collected information about the lifestyle in this village, which were compared with the data obtained through the bibliographic review on Kayapó culture. In this sense, the analysis of the obtained result was based on studies of authors as Meliá (1979), who emphasizes, concerning indigenous education, that indians has already an education system of their own; Raimundo Nascimento (2017), who considers the claims of indigenous movements which took place in the 1970s and the Federal Constitution of 1988 as a start point, because the Constitution states Brazil as a multicultural State and establishes the indigenous school education as an intercultural, differentiated, specific and bilingual education, which is a possible direction in the construction of a school that consider the rights and the differences of the indigenous people; Adir Nascimento (2004), who stimulates the dialogue that helps the reflective mediation so that the school is reinvented by giving a new meaning to the pedagogical and educational practices according to the specificity of each indigenous community; and Freire (1996), who discuss the school environment in a pedagogical universe, trying to clarify that the educator can not transform the educational experience into something mechanistic, but to teach considering the worldly wisdom of the students